2020
DOI: 10.1007/s11892-020-01316-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Amniotic Membrane Derivatives and Their Potential in Regenerative Medicine

Abstract: Purpose of Review During the last decades, the field of regenerative medicine has been rapidly evolving. Major progress has been made in the development of biological substitutes applying the principles of cell transplantation, material science, and bioengineering. Recent Findings Among other sources, amniotic-derived products have been used for decades in various fields of medicine as a biomaterial for the wound care and tissue replacement. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 114 publications
3
55
0
Order By: Relevance
“…Moreover, hAECs have tri-mesodermal lineage differentiation potential; they can produce osteogenic, adipogenic, and chondrogenic lineages under appropriate culture conditions [ 17 ]. Notably, hAECs have low expression levels of human leukocyte antigens (including HLA-A, HLA-B, and HLA-C and HLA-DR), which are key antigens involved in recipient rejection [ 1 , 18 ]. A study confirmed that intravenous administration of hAECs did not result in hemolysis, allergic reactions, toxicity, or tumor formation, which demonstrated that hAECs were systematically safe [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, hAECs have tri-mesodermal lineage differentiation potential; they can produce osteogenic, adipogenic, and chondrogenic lineages under appropriate culture conditions [ 17 ]. Notably, hAECs have low expression levels of human leukocyte antigens (including HLA-A, HLA-B, and HLA-C and HLA-DR), which are key antigens involved in recipient rejection [ 1 , 18 ]. A study confirmed that intravenous administration of hAECs did not result in hemolysis, allergic reactions, toxicity, or tumor formation, which demonstrated that hAECs were systematically safe [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perinatal stem cells are not immunogenic and are in a state of immune tolerance. Perinatal stem cells do not express HLA class II antigens (HLA-DR) or the co-stimulatory molecules CD40, CD80, and CD86 that are required for T cell activation [ 121 , 122 ]. However, HLA-DR expression increases after in vitro stimulation with IFN-ɣ or when cultured without serum.…”
Section: Immunological Properties Of Perinatal Stem Cellsmentioning
confidence: 99%
“…However, MSCs harvesting is an invasive procedure, their numbers and properties decrease with donor’s age, and they have a potential for tumorigenicity [85,86]. Amniotic epithelial cells (AECs) are an alternative source of cells with similar properties [87]. These cells are derived from the amniotic membrane and are involved in the modulation of materno‐fetal tolerance during pregnancy [88].…”
Section: Improved Pseudo‐islets: the Benefits Of Adding Supporting Cementioning
confidence: 99%